Integration social media technology and ethical collaborative learning - Ataie, Fariba; Shah, Asadullah; Imtiaz Ali, Najma (Science Publishing Corporation Inc, 2018)
The research aimed to design and evaluate an innovative Web 2.0-based collaborative learning with the Islamic ethical system to support Islamicisation and the practice of Islam as a way of life that is the main goal of Islamic education. This is in response to the lesser amount of focus in Islamic education on the real example of integrating ICT into the collaborative learning process that could support social constructivist learning goals and skills for use of Islamic knowledge in daily life. The most important argument is that the students should be given an appropriate and practical platform where they can practice collaboratively and share their experiences that design science research methodology and Facebook features in this study could support these needs and arguments. Expert review, user testing were conducted and quality, effectiveness and usability of developed Web 2.0-based collaborative learning confirmed.